Hidden talent : the emergence of Hollywood agents - Kemper, Tom. (Berkeley : University of California Press, 2010)
This is a history of Hollywood agents as they rose in the studio system in the late 1920s and early 1930s up through the 1940s, demonstrating the central role they played in the classical Hollywood period.
City of agents : the power of place -- Revenge of the agent : Myron Selznick -- A percentage of power : small agents -- Charisma and contracts : Charles Feldman -- Numbers and niches : boutique agencies -- Sealing the deal : the contract industry -- My man Myron : power and persuasion -- What made Myron run? : the whole equation -- Tall in the saddle : agents in the producer's chair -- The deal factory : new fortunes in the forties -- Epilogue: The corporate era : changing channels.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Theatrical agents -- California -- Los Angeles -- History -- 20th century; Theatrical agencies -- California -- Los Angeles -- History -- 20th century; Motion picture industry -- California -- Los Angeles -- History -- 20th century; Agents théâtraux -- Californie -- Los Angeles -- Histoire -- 20e siècle.; Agences artistiques -- Californie -- Los Angeles -- Histoire -- 20e siècle.; Cinéma -- Industrie -- Californie -- Los Angeles -- Histoire -- 20e siècle.; PERFORMING ARTS -- Business Aspects; PERFORMING ARTS -- Film & Video -- General; Motion picture industry; Theatrical agencies; Theatrical agents; California -- Los Angeles; Filmagent; Los Angeles- Hollywood; 1900-1999; Geschichte 1925-1949; History